Archival Human Resources Development Strategy in The Implementation of Electronic-Based Government Systems - Puspita, Wirastri Dyah; Herawan, Lufi (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
The development of information and communication technology had a fundamental impact on the archives sector, including changing the way managed archives conventionally to digitally. Archival human resources play an important role in the implementation of the Electronic Based Government System not only in terms of quantity but also quality. However, to answer this, regulations regarding the functions, duties and authority of archival human resources are no longer relevant, there is no road map for the development of archival human resources, and there is no database for developing archival human resources, also the test not yet able to measure the competency archival human resources in implementing Electronic Based Government System. This research aims to provide input to policy makers for the development of archival human resources in the implementation of SPBE. The research was carried out using descriptive methods in the form of library research, where data was taken from books, articles, regulations and other document sources. The analysis uses SWOT to obtain recommendations for problem solving which are outlined in the strategy: compiling a road map for developing archival human resources, determining effective methods of active discussion and knowledge sharing, building partnerships with related parties, empowering key functional expert archivists in developing archival human resources in the Electronic Based Government System era.